High-dose therapy and autologous hematopoietic stem cell transplant in T-cell lymphoma: a single center experience. Issue 8 (August 2014) - Cairoli, Anne; Ketterer, Nicolas; Barelli, Stefano; Duchosal, Michel A.
Abstract We report here the long-term outcome of autologous stem cell transplant in peripheral T-cell lymphoma (PTCL). Forty-three consecutive patients with PTCL diagnosed between 2000 and 2011 were treated with high-dose chemotherapy (HDCT) and autologous stem cell transplant (ASCT) in our center. Diagnoses included PTCL-not otherwise specified (n = 19), anaplastic large cell lymphoma (n = 11), angioimmunoblastic T-cell lymphoma (n = 5), enteropathy-associated T-cell lymphoma (n = 5) and other rare subtypes (n = 3). Thirty-six patients with a median age of 50 years (range 22–65) were transplanted in first response and seven after relapse. After a median follow-up of 63 months, estimated overall survival at 12 years was 40%, progression-free survival at 12 years was 34% and event-free survival at 12 years was 30%. On univariate analysis, age less than 50 years and no B symptoms at diagnosis were significantly associated with prolonged overall and progression-free-survival. HDCT/ASCT for peripheral T-cell lymphoma can lead to long-term survival for patients responding to induction chemotherapy.